A history of the South African Rugby Referees' Society, 1914-1981 - Hoefnagels, Johannes Atonius Marie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. of Phys. Ed.) -- University of Stellenbosch, 1983.